An mHealth Design to Promote Medication Safety in Children with Medical Complexity - Jolliff, Anna; Coller, Ryan J.; Kearney, Hannah; Warner, Gemma; Feinstein, James A.; Chui, Michelle A.; O'Brien, Steve; Willey, Misty; Katz, Barbara; Bach, Theodore D.; Werner, Nicole E. (Applied Clinical Informatics, 2024)
Background Children with medical complexity (CMC) are uniquely vulnerable to medication errors and preventable adverse drug events because of their extreme polypharmacy, medical fragility, and reliance on complicated medication schedules and routes managed by undersupported family caregivers. There is an opportunity to improve CMC outcomes by designing health information technologies that support medication administration accuracy, timeliness, and communication within CMC caregiving networks.Objectives The present study engaged family caregivers, secondary caregivers, and clinicians who work with CMC in a codesign process to identify: (1) medication safety challenges experienced by CMC caregivers and (2) design requirements for a mobile health application to improve medication safety for CMC in the home.Methods Study staff recruited family caregivers, secondary caregivers, and clinicians from a children's hospital-based pediatric complex care program to participate in virtual codesign sessions. During sessions, the facilitator-guided codesigners in generating and converging upon medication safety challenges and design requirements. Between sessions, the research team reviewed notes from the session to identify design specifications and modify the prototype. After design sessions concluded, each session recording was reviewed to confirm that all designer comments had been captured.Results A total of N = 16 codesigners participated. Analyses yielded 11 challenges to medication safety and 11 corresponding design requirements that fit into three broader challenges: giving the right medication at the right time; communicating with others about medications; and accommodating complex medical routines. Supporting quotations from codesigners and prototype features associated with each design requirement are presented.Conclusion This study generated design requirements for a tool that may improve medication safety by creating distributed situation awareness within the caregiving network. The next steps are to pilot test tools that integrate these design requirements for usability and feasibility, and to conduct a randomized control trial to determine if use of these tools reduces medication errors.
Keywords: medication management; polypharmacy; pediatrics; user-centered design; social networks